EFIKASI DIRI DAN MOTIVASI TERHADAP KEBERHASILAN USAHA PADA USAHA FOTO COPY DAN ALAT TULIS KANTOR DI KECAMATAN PANYABUNGAN KABUPATEN MANDAILING NATAL - RINA WAHYUNI DAULAY; frida ramadini (Jurnal Media Informasi Manajemen, 2013)
Abstract The purpose of this study was to determine the effect of Self-Efficacy, Motivation Of Business Success In Entrepreneur copy of The District Panyabungan Mandailing Natal district. The method of analysis used is deskrptif analysis methods and statistical multiple regression analysis. Techniques of data collection were interviews, questionnaires, study dokumentsasi. The formulation of the problem in this research is to investigate and analyze the effect of self efficacy, motivation to Business Success In Entrepreneur photocopy In Sub District Panyabungan Mandailing Natal. The results of this study showed that the test results to the value of 36.814 F indicates that the variable which consists of self-efficacy and motivation can be used to estimate the success of the business in the District Panyabungan. T significant test results (t test) states that the variables have a significant effect is self efficacy variable (X1), with a significant level of 0.016 <0.05, while the variable motivation (X2) should be increased again in order to estimate the effort success copy in Sub Panyabungan. Results determinant coefficient () is 0.156 meaning that 15.6% have the business success copy can be explained by the variable efficacy and motivation have a close enough relationship to the success of businesses in the district a copy of Panyabungan. Keywords: self-efficacy, motivationandbusiness success